Effect of Various Concentration of Glycerol on Post Thaw Quality of Holstein-Friesian Bull Semen - Bakhsh, Sakhi; Kumbhar, Hamzo Khan; Raja, Rameez; Kaleri, Hubdar Ali; Solangi, Ghulam Mustafa; Mangi, Raza Ali; Mangrio, Zahid Ali; Naseem, Mohammad; Bozdar, Zakir Hussain; Anwar, Ali; Arif, Mohammad; Bhuptani, Deepesh Kumar; et al. (Journal of Agriculture and Veterinary Science, 2023)
The aims of study were to compare the glycerol concentration in Tris, Citric acid Egg yolk diluents on the quality of Holstein Friesian frozen semen. Three Holstein Friesian bulls were maintained to collect the 45 semen samples. Total of 15 ejaculates sample were collected from each bull. Fresh semen was evaluated for volume, color, pH, concentration and motility. Every collection of 3 ejaculate was pooled and examined. Each pooled semen sample was divided in to three experimental extenders A, B, C, glycerol was used as diluents at 7, 6, 5%, Pencillin (1000 I.U/ml) and streptomycin (1000g/ml) were added to each diluent. Immediately after completion of the semen extension process, the post dilution motility percentage of each extender was noted. After 24 hours of freezing and storage liquid nitrogen -196 oC, three sample straws from each glycerol concentration were taken out and thawed in water bath at 370C for 15 seconds. After thawing the semen was tested by sperm quality analyzer SQA vb for bull post thaw motility % , progressive motility %, average pathway velocity µm/s, straight-line velocity µm/s, curvilinear velocity µm/s varied significantly between 5, 6 and 7% glycerol concentration  to treatment p>0.05. Results of the experiment demonstrated that post thawed sperm motility in the semen preserved with 7% glycerol higher than other levels of glycerol, PTM (49.64%), PM (34.76%), VAP (94.92 um/s), VSL(85.36 um/s), VCL(165.42 um/s). It was concluded that 7% glycerol is recommended for freezing media regarding with best result on post-thaw quality of Holsteins-Friesian bull semen.
Keywords: Semen; Glycerol; Post thaw quality; Holstein Frisian